Optimizing Legal Protection for Divorce Outside of Court: Study of the Need for Divorce Isbat in the Indonesian Legal System - Dedi Kusnandar; Fitriani Rahma (Indonesian Journal of Islamic Law, 2023)
This research examines the dualism of religious law and national law in the context of divorce in Indonesia, which raises significant legal and social dilemmas and challenges. This study uses a descriptive-analytic qualitative method with a normative juridical approach to analyze differences in divorce recognition under religious law and national law, as well as its impact on access to justice and legal protection, especially for women. This research identifies that discrepancies in divorce recognition cause various legal and social obstacles, such as difficulties in obtaining maintenance, division of assets, and child custody. As a solution, this study proposes the application of the concept of "divorce isbat" as a mechanism that allows official recognition of divorces carried out outside formal courts, offering higher legal certainty and more effective protection. This research highlights the importance of engaging cross-sectoral stakeholders, including religious leaders, legal practitioners, and civil society organizations, in supporting inclusive and effective legal reform. The implication of these findings is the need for legal reform that harmonizes religious law with national law to strengthen the integrity of the justice system and improve social justice.